Application of Phase Change Materials to Reduce Heat Related Risks During Extreme Heat Waves in Australian Dwellings. (June 2016) - Ramakrishnan, Sayanthan; Wang, Xiaoming; Sanjayan, Jay; Wilson, John
Abstract: This study investigates the effect of phase change materials (PCMs) in reducing potential heat stress risks in non-air-conditioned buildings during heat wave periods, such as that occurred in Melbourne, 2009. A residential house is refurbished with the installation of shape-stabilized phase change material as inner linings of walls and ceiling. Dynamic thermal simulations were performed in EnergyPlus for the heat wave period in Melbourne, Australia. Discomfort Index (DI) has been used as an indicator for the heat stress evaluation. From the simulation, it was observed that the incorporation of PCM in combination with night ventilation could reduce the hours of severe heat stress risks by up to 32%. Therefore, it is foreseeable that the application of PCM would have potential for minimizing the effect of heat waves on the occupant health and comfort in non-air-conditioned buildings. However, proper building design such as night ventilation is essential for the efficient utilization of phase change materials during heat wave period.